A typical defect and repair test method for composite materials

By designing and analyzing the intact, defect-containing and repaired test pieces of the composite material, the repair problem lacking quantitative analysis in the prior art is solved, and a quantitative evaluation of typical defects and repair effects is achieved.

CN115728108BActive Publication Date: 2025-04-22CHINA HELICOPTER RES & DEV INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211460325.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2025-04-22
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

The existing repair methods for composite structures lack quantitative analysis of damage repair strength, and cannot effectively evaluate the impact of typical defects on the mechanical properties of composite materials.

Method used

Mechanical performance analysis, including compression performance test and load-strain curve analysis, is carried out by designing intact, defect-containing and repaired composite test pieces, to explore the impact of typical defects on the mechanical properties of composite materials and the repair effect.

Benefits of technology

Quantitative analysis of typical defects and repair effects is achieved, which can effectively evaluate the impact of defects on the mechanical properties of composite materials and provide strength data after repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115728108B_ABST
    Figure CN115728108B_ABST
Patent Text Reader

Abstract

The present application provides a method for testing typical defects and repairs of composite materials, the method comprising: making an intact test piece; making a test piece containing defects; making a test piece after repair; performing mechanical property analysis on the test piece containing defects and the test piece after repair based on the intact test piece; by reasonably designing the test piece layup, the size and location of defects can be controlled, and typical failures of delamination and debonding generated during the molding and use of two types of composite materials can be simulated to the maximum extent, and then the influence of typical defects on the mechanical properties of composite materials can be explored through strength tests, and quantitative analysis of the influence of defects and repair effects can be performed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of composite material structures, and in particular relates to a typical defect of a composite material and a repair test method. Background Art

[0002] With the development of composite material technology, the proportion of composite materials used in helicopter fuselage structures is increasing. Composite material structures include laminated structures and honeycomb sandwich structures. According to previous usage experience, laminated structure delamination and honeycomb sandwich structure debonding are two typical and high-incidence failures. Laminated structure delamination refers to the peeling phenomenon between layers in the laminated structure, and honeycomb sandwich structure debonding refers to the peeling phenomenon between the honeycomb and the panel.

[0003] The delamination of laminated structures and the debonding of honeycomb sandwich structures seriously affect the bearing capacity of composite structures, and delamination damage expansion may occur.

[0004] The existing repair methods only determine whether the repair means is effective, but lack the strength basis before and after the repair of the defects, and cannot conduct a quantitative analysis of the damage repair strength. Summary of the invention

[0005] In view of the above technical problems, the present application provides a typical defect and repair test method for composite materials, the method comprising:

[0006] Make a complete test piece;

[0007] Make test pieces with defects;

[0008] Make test pieces after repair;

[0009] The mechanical properties of the defective test piece and the repaired test piece are analyzed based on the intact test piece.

[0010] Preferably, the manufacturing of the intact test piece comprises:

[0011] Making laminated structure intact test pieces and making honeycomb sandwich structure intact test pieces;

[0012] The laminated structure intact test piece includes a laminated structure and a reinforcement. The laminated structure material is 5224 / CF3052 / 39, and the ply arrangement is 45° / 0° staggered.

[0013] Among them, the intact test piece of the honeycomb sandwich structure includes honeycomb core material, upper surface intact structure, lower surface intact structure and edge sealing filler. The honeycomb core material is NH-1-1.83-48-δ20, the upper surface intact structure material is 5224 / CF3052 / 39, the plying method is 45° / 0° staggered arrangement, and the plying of the lower surface intact structure is symmetrical with the plying of the lower surface intact structure.

[0014] Preferably, reinforcing members are arranged in the clamping area of ​​the laminated structure test piece, and edge sealing fillers are filled in the clamping area of ​​the honeycomb sandwich structure test piece to increase the supporting stiffness of the supporting area of ​​the test piece.

[0015] Preferably, the step of preparing a test piece containing defects comprises:

[0016] Laminated structure defect test pieces and honeycomb sandwich structure defect test pieces;

[0017] The laminated structure defect test piece includes a laminated structure, a defective ply and a reinforcement; wherein the defective ply is two layers of Teflon film;

[0018] Among them, the honeycomb sandwich structure defect test piece includes honeycomb core material, upper surface intact structure, lower surface intact structure, edge sealing filler and defective ply;

[0019] Preferably, different defect positions are simulated by laying Teflon films between different layers, and different defect sizes are simulated by adjusting the size of the Teflon films.

[0020] Preferably, the manufacturing of the repaired test piece includes: a laminated structure repair test piece and a honeycomb sandwich structure repair test piece;

[0021] The laminated structure repair test piece includes a laminated structure to be repaired, a film, a repair ply and a reinforcement. The laminated structure to be repaired is made of 5224 / CF3052 / 39, and the plying method is 45° / 0° staggered. The plying is performed in a step-by-step manner at the preset layering position, and the step amount between each layer is 15mm. The film is laid on the laminated structure to be repaired, and the repair ply is laid on the film. The materials used are the same as those of the laminated structure to be repaired, and the plying angle is the same as the original ply, and the step overlap between each layer is 15mm.

[0022] Among them, the honeycomb sandwich structure repair test piece includes the honeycomb core material to be repaired, the upper surface structure to be repaired, the intact structure on the lower surface, 17# filler, adhesive film, repair ply and edge-sealing filler. The upper surface ply structure material to be repaired is 5224 / CF3052 / 39, and the ply method is 45° / 0° staggered arrangement. 17# filler is filled in the area to be repaired, the adhesive film is laid on the upper surface structure to be repaired, and the repair ply is laid on the adhesive film. The materials used are the same as those of the upper surface structure to be repaired, the ply angle is the same as the original ply, and the step overlap between each layer is 15mm.

[0023] Preferably, a layer of adhesive film is laid on the upper surface of the structure to be repaired to bond the structure to be repaired and the repair layer to ensure the bonding strength between the layers.

[0024] Preferably, the mechanical properties analysis of the defective test piece and the repaired test piece based on the intact test piece includes:

[0025] Compression performance tests were carried out on intact specimens, defective specimens and repaired specimens, and the generated load-strain curves were analyzed. The critical instability stress and ultimate failure strength of the three types of specimens were compared, the influence of typical defects on the mechanical properties of composite materials was explored, and a quantitative analysis of the defect impact and repair effect was performed.

[0026] Beneficial technical effects of this application:

[0027] By rationally designing the layup of the test pieces, the size and location of defects can be controlled, and typical failures of delamination and debonding occurring during the molding and use of composite materials can be simulated to the maximum extent. Furthermore, the influence of typical defects on the mechanical properties of composite materials can be explored through strength tests, and quantitative analysis of the impact of defects and repair effects can be performed.

[0028] By using the control variable method, the influence of a single fault parameter on the mechanical properties of the test piece can be compared. When the defect area is the same, the three types of test pieces, namely, intact test pieces, defective test pieces, and repaired test pieces, can be compared in pairs; when the same treatment measures are taken, the influence of the defect size on the mechanical properties of the test piece can be examined. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the structure of a laminated structure intact test piece provided in an embodiment of the present application;

[0030] Figure 2 A schematic diagram of a typical layer structure of a laminated structure intact test piece provided in an embodiment of the present application;

[0031] Figure 3 A schematic diagram of the structure of a good test piece of a honeycomb sandwich structure provided in an embodiment of the present application;

[0032] Figure 4 A schematic diagram of a typical layer structure of a good test piece of a honeycomb sandwich structure provided in an embodiment of the present application;

[0033] Figure 5 A schematic diagram of the structure of a laminated structure defect test piece provided in an embodiment of the present application;

[0034] Figure 6 A schematic diagram of a typical layer structure of a laminated structure defect test piece provided in an embodiment of the present application;

[0035] Figure 7 A schematic diagram of the structure of a honeycomb sandwich structure defect test piece provided in an embodiment of the present application;

[0036] Figure 8 A schematic diagram of a typical layer structure of a honeycomb sandwich structure defect test piece provided in an embodiment of the present application;

[0037] Fig. 9 A schematic diagram of a typical layer structure of a laminated structure repair test piece provided in an embodiment of the present application;

[0038] Fig.10 A schematic diagram of a typical layer structure of a honeycomb sandwich structure repair test piece provided in an embodiment of the present application;

[0039] Among them, 1-laminated structure; 2-reinforcement; 3-honeycomb core material; 4-upper surface intact structure; 5-lower surface intact structure; 6-edge sealing filler; 7-defective ply; 8-laminated structure to be repaired; 9-adhesive film; 10-repair ply; 11-honeycomb core material to be repaired; 12-upper surface structure to be repaired; 13-17# filler. DETAILED DESCRIPTION

[0040] It should be noted that according to the typical defect test and repair test method of the present application, through the design of laminated structure and honeycomb sandwich structure, artificial simulation of composite material test pieces with defects and after repair, and design of different defect sizes and defect positions, taking the compression strength test as an example, the strength values ​​of the intact test piece, the defective test piece and the repaired test piece are compared to explore the influence of typical defects and repairs on the mechanical properties of composite material structures.

[0041] See also Figure 1-10 , in the embodiments of the present application, the present application includes two structural forms: a laminated structure and a honeycomb sandwich structure;

[0042] The intact laminated structure test piece includes a laminated structure and reinforcements; the laminated structure material is 5224 / CF3052 / 39, with a total of 12 layers, and the layering method is 45° / 0° staggered arrangement; in order to increase the support stiffness of the test piece's supporting area, reinforcements are bonded to the upper and lower surfaces at both ends of the test piece for local reinforcement.

[0043] The laminated structure defect test piece includes a laminated structure, a defective ply and a reinforcement. The defective ply is two layers of Teflon film. By laying Teflon film between different plies, different defect positions are simulated, and by adjusting the size of Teflon film, different defect sizes are simulated.

[0044] The laminated structure repair test piece includes a laminated structure to be repaired, a film, a repair ply and a reinforcement. The laminated structure to be repaired is made of 5224 / CF3052 / 39, with n layers in total. The plying method is a 45° / 0° staggered arrangement. The plying is performed in steps at the preset layering position, with a step amount of 15mm between each layer. The film is laid on the laminated structure to be repaired, and the repair ply is laid on the film. The materials used are the same as those of the laminated structure to be repaired, the plying angle is the same as the original ply, and the step overlap between each layer is 15mm.

[0045] In a feasible implementation, the present application designs test pieces with different defect locations, defect sizes and corresponding repairs, and compares the influence of defect size on test pieces No. 1-3, and the influence of defect location on test pieces No. 1 and No. 4, test pieces No. 2 and No. 5, and test pieces No. 3 and No. 6, as shown in Table 1.

[0046] Table 1

[0047] serial number Complete lay-up Delamination defect location Defect size / mm 1 <![CDATA[[45° / 0°] 3s ]]> 1 / 6 Thickness φ20mm 2 <![CDATA[[45° / 0°] 3s ]]> 1 / 6 thickness φ40mm 3 <![CDATA[[45° / 0°] 3s ]]> 1 / 6 Thickness φ80mm 4 <![CDATA[[45° / 0°] 3s ]]> 1 / 3 thickness φ20mm 5 <![CDATA[[45° / 0°] 3s ]]> 1 / 3 thickness φ40mm 6 <![CDATA[[45° / 0°] 3s ]]> 1 / 3 thickness φ80mm

[0048] Among them, the intact test piece of the honeycomb sandwich structure includes a honeycomb core material, an upper surface intact structure, a lower surface intact structure and an edge sealing filler. The honeycomb core material is NH-1-1.83-48-δ20, and the upper surface intact structure material is 5224 / CF3052 / 39. The plying method is a 45° / 0° staggered arrangement, and the upper surface intact structure is symmetrical with the lower surface intact structure. In order to increase the support stiffness of the clamping area of ​​the test piece, edge sealing fillers are used at both ends of the test piece for edge sealing.

[0049] Among them, the honeycomb sandwich structure defect test piece includes honeycomb core material, upper surface intact structure, lower surface intact structure, edge sealing filler and defective ply; the honeycomb sandwich structure repair test piece includes honeycomb core material to be repaired, upper surface structure to be repaired, lower surface intact structure, 17# filler, adhesive film, repair ply and edge sealing filler. The upper surface ply structure to be repaired is made of 5224 / CF3052 / 39, and the plying method is 45° / 0° staggered arrangement. 17# filler is filled in the area to be repaired, adhesive film is laid on the upper surface structure to be repaired, and the repair ply is laid on the adhesive film. The materials used are the same as those of the upper surface structure to be repaired, and the ply angle is the same as the original ply. The step overlap between each layer is 15mm.

[0050] In a feasible implementation, the present application designs test pieces with different defect locations, defect sizes and corresponding repairs, and compares the influence of defect size on test pieces No. 7-9, and the influence of defect location on test pieces No. 7 and No. 10, test pieces No. 8 and No. 11, and test pieces No. 9 and No. 12, as shown in Table 2.

[0051] Table 2 (Note N is honeycomb core material)

[0052] serial number Complete lay-up Defect size / mm 7 [45° / 0° / 45° / N]s φ20mm 8 [45° / 0° / 45° / N]s φ40mm 9 [45° / 0° / 45° / N]s φ80mm 10 [45° / 0° / 45° / 0° / 45° / 0° / N]s φ20mm 11 [45° / 0° / 45° / 0° / 45° / 0° / N]s φ40mm 12 [45° / 0° / 45° / 0° / 45° / 0° / N]s φ80mm

[0053] It should be noted that:

[0054] 1) By arranging reinforcement members in the clamping area of ​​the laminated structure test piece and filling edge sealing fillers in the clamping area of ​​the honeycomb sandwich structure test piece, the support stiffness of the clamping area of ​​the test piece is increased;

[0055] (2) Laying two layers of Teflon film between the layers simulates the delamination between the layers of the laminated structure; Laying two layers of Teflon film between the honeycomb core material and the upper surface structure simulates the debonding defect of the honeycomb sandwich structure;

[0056] (3) By laying Teflon film between different layers, different defect locations are simulated, and by adjusting the size of the Teflon film, different defect sizes are simulated;

[0057] (4) Lay a layer of adhesive film on the upper surface of the structure to be repaired to bond the structure to be repaired and the repair layer to ensure the bonding strength between the layers;

[0058] (5) Lay n layers of repair plies in sequence, with an overlap of 15 mm between each layer, and the ply angle is the same as the original ply, with a unified repair standard, and the test results of the test pieces after the repair are reliable;

[0059] (6) By designing three types of test pieces: intact test pieces, defective test pieces, and repaired test pieces, the effects of typical defects and repairs on the mechanical properties of composite structures can be explored through strength tests.

[0060] The test piece design described in this application has the following advantages:

[0061] ① By rationally designing the layup of the test piece, the size and location of defects can be artificially controlled, and the typical failures of delamination and debonding generated during the molding and use of composite materials can be simulated to the maximum extent. Then, the influence of typical defects on the mechanical properties of composite materials can be explored through strength tests, and quantitative analysis of the impact of defects and repair effects can be carried out.

[0062] ② By using the control variable method, the influence of a single fault parameter on the mechanical properties of the test piece can be compared. When the defect area is consistent, the three types of test pieces, namely, intact test pieces, defective test pieces, and repaired test pieces, can be compared in pairs. When the same treatment measures are taken, the influence of the defect size on the mechanical properties of the test piece can be examined.

[0063] In other embodiments of the present application, the laminated structure intact test piece includes a laminated structure 1 and a reinforcement 2, such as Figure 1 The laminate structure 1 material is 5224 / CF3052 / 39, with 12 layers in total, and the plying method is 45° / 0° staggered arrangement. The plying diagram is shown in Figure 2 shown.

[0064] In other embodiments of the present application, the intact test piece of the honeycomb sandwich structure includes a honeycomb core material 3, an upper surface intact structure 4, a lower surface intact structure 5 and an edge sealing filler 6. The material of the honeycomb core material 3 is NH-1-1.83-48-δ20, the material of the upper surface intact ply 4 is 5224 / CF3052 / 39, there are 3 layers in total, the plying method is 45° / 0° staggered arrangement, the upper surface intact structure 5 is symmetrical with the lower surface intact structure 4, and the plying schematic diagram is as shown in Figure 4 shown.

[0065] In other embodiments of the present application, the laminated structure defect test piece includes a laminated structure 1, a defective ply 7 and a reinforcement 2; wherein the defective ply 7 is two layers of Teflon film.

[0066] In other embodiments of the present application, the honeycomb sandwich structure defect test piece includes a honeycomb core material 3, an upper surface intact structure 4, a lower surface intact structure 5, an edge sealing filler 6 and a defective ply 7, wherein the defective ply 7 is two layers of Teflon film, and the ply schematic diagram is as shown in FIG. Figure 8 shown.

[0067] In other embodiments of the present application, the laminated structure repair test piece includes a laminated structure to be repaired 8, a film 9, a repair ply 10 and a reinforcement 2. The material of the laminated structure to be repaired 8 is 5224 / CF3052 / 39, there are 12 plies in total, the plying method is 45° / 0° staggered arrangement, the plying is stepped at the preset layering position, and the step amount between each layer is 15mm. The film 9 is laid on the laminated structure to be repaired 8, and the repair ply 10 is laid on the film 9. The material used is the same as that of the laminated structure to be repaired 8, the plying angle is the same as the original ply, and the step overlap amount between each layer is 15mm; Fig. 9 shown.

[0068] In other embodiments of the present application, the honeycomb sandwich structure repair test piece includes a honeycomb core material 11 to be repaired, an upper surface structure to be repaired 12, a lower surface intact structure 5, a 17# filler 13, a film 9, a repair ply 10 and an edge-sealing filler 6. The material of the upper surface ply structure 12 to be repaired is 5224 / CF3052 / 39, with a total of 3 layers, and the plying method is 45° / 0° staggered arrangement, the 17# filler 13 is filled in the area to be repaired, the film 9 is laid on the upper surface structure to be repaired 12, and the repair ply 10 is laid on the film 9. The materials used are the same as those of the upper surface structure to be repaired 12, the ply angle is the same as the original ply, the step overlap between each layer is 15mm, and the ply is as follows: Fig.10 shown.

Claims

1. A typical defect and repair test method for composite materials, characterized in that: The method comprises: Make a complete test piece; Make test pieces with defects; Make test pieces after repair; Performing mechanical property analysis on the defective test piece and the repaired test piece based on the intact test piece; Wherein, the method of making a test piece containing defects comprises: Laminated structure defect test pieces and honeycomb sandwich structure defect test pieces; The laminated structure defect test piece includes a laminated structure, a defective ply and a reinforcement; wherein the defective ply is two layers of Teflon film; The honeycomb sandwich structure defect test piece includes a honeycomb core material, an upper surface intact structure, a lower surface intact structure, an edge sealing filler and a defective ply; wherein the defective ply is two layers of Teflon film; By laying Teflon film between different layers, different defect locations can be simulated; by adjusting the size of Teflon film, different defect sizes can be simulated; The repaired test pieces include: laminated structure repair test pieces and honeycomb sandwich structure repair test pieces; The laminated structure repair test piece includes a laminated structure to be repaired, a film, a repair ply and a reinforcement. The laminated structure to be repaired is made of 5224 / CF3052 / 39, and the plying method is 45° / 0° staggered. The plying is performed in a step-by-step manner at the preset layering position, and the step amount between each layer is 15mm. The film is laid on the laminated structure to be repaired, and the repair ply is laid on the film. The materials used are the same as those of the laminated structure to be repaired, and the plying angle is the same as the original ply, and the step overlap between each layer is 15mm. Among them, the honeycomb sandwich structure repair test piece includes the honeycomb core material to be repaired, the upper surface structure to be repaired, the intact structure on the lower surface, 17# filler, adhesive film, repair ply and edge-sealing filler; the upper surface ply structure material to be repaired is 5224 / CF3052 / 39, the plying method is 45° / 0° staggered arrangement, 17# filler is filled in the area to be repaired, the adhesive film is laid on the upper surface structure to be repaired, and the repair ply is laid on the adhesive film. The materials used are the same as those of the upper surface structure to be repaired, the ply angle is the same as the original ply, and the step overlap between each layer is 15mm; Lay a layer of adhesive film on the surface of the structure to be repaired to bond the structure to be repaired and the repair layer to ensure the bonding strength between the layers; The mechanical properties of the defective test piece and the repaired test piece are analyzed based on the intact test piece, including: Compression performance tests were carried out on intact specimens, defective specimens and repaired specimens, and the generated load-strain curves were analyzed. The critical instability stress and ultimate failure strength of the three types of specimens were compared, the influence of typical defects on the mechanical properties of composite structures was explored, and a quantitative analysis of the defect impact and repair effect was performed.

2. The method according to claim 1, characterized in that: The prepared test piece comprises: Making laminated structure intact test pieces and making honeycomb sandwich structure intact test pieces; The laminated structure intact test piece includes a laminated structure and a reinforcement. The laminated structure material is 5224 / CF3052 / 39, and the ply arrangement is 45° / 0° staggered. Among them, the intact test piece of the honeycomb sandwich structure includes honeycomb core material, upper surface intact structure, lower surface intact structure and edge sealing filler. The honeycomb core material is NH-1-1.83-48-δ20, and the upper surface intact structure material is 5224 / CF3052 / 39. The ply arrangement is 45° / 0° staggered, and the upper surface intact structure is symmetrical with the lower surface intact structure.

3. The method according to claim 2, characterized in that By arranging reinforcements in the clamping area of ​​the laminated structure test piece and filling the clamping area of ​​the honeycomb sandwich structure test piece with edge sealing fillers, the supporting stiffness of the supporting area of ​​the test piece is increased.

Citation Information

Patent Citations

  • Repairing method for honeycomb sandwich structure

    CN105173109A

  • Method for preparing defect test piece of composite material

    CN106769302A